Anti-thrombotic effect of bivalirudin compared with eptifibatide and unfractionated heparin in diabetic patients - Lev, Eli I.; Patel, Rajnikant; Karim, Azim; Kleiman, Amanda; Badimon, Juan J.; Kleiman, Neal S. (Thrombosis and Haemostasis, 2006)
Patients with diabetes who undergo percutaneous coronary intervention (PCI) are at high risk for thrombotic complications following the procedure. We sought to compare the anti-thrombotic effect of bivalirudin to that of eptifibatide plus unfractionated heparin in diabetic patients undergoing elective PCI. Thirty diabetic patients were randomized to receive during PCI either bivalirudin (bivalirudin group, n=15) or eptifibatide plus heparin (eptifibatide group, n=15) at standard dosing regimens. The drugs were continued for 20 minutes (bivalirudin) or 18 hours (eptifibatide) after PCI. Blood thrombogenicity was assessed using the Badimon ex vivo perfusion chamber. Each patient underwent two perfusion studies – at baseline (on aspirin and clopidogrel) and 15–20 minutes following PCI. Perfusion studies were performed at rheologic conditions of low and high shear rates (LSR, HSR). Porcine aortic tunica media served as the thrombogenic substrate. Aortic specimens were stained for total platelet-thrombus and fibrin deposition. Thrombus area was measured using computerized planimetry. There were no differences in clinical characteristics or baseline thrombus area between the two groups. Total platelet-thrombus area was reduced significantly in both groups, but the degree of reduction was lower in the bivalirudin group compared with the eptifibatide group (HSR: 69.5% vs. 89.3% reduction, respectively, P=0.04; LSR: 50.6% vs. 73.2%, P=0.03). Fibrin deposition was reduced in both groups by 47–49%. In conclusion, both bivalirudin and the combination of eptifibatide plus heparin, given to diabetic patients during PCI, achieved marked reductions in total thrombus formation and fibrin deposition. However, glycoprotein IIb/IIIa inhibition by eptifibatide causeda more pronounced reduction in thrombus formation.
Keywords: Antithrombin; diabetes/metabolic disorders; platelet pharmacology; antiplatelet drugs; direct antithrombin agents